2007
DOI: 10.1109/tie.2006.885454
|View full text |Cite
|
Sign up to set email alerts
|

Comments on “Unified Analysis of Switched-Capacitor Resonant Converters”

Abstract: The realization of line and load regulation in switchedcapacitor (SC)-based converters is discussed. A duty-cycle control is based on partial charging of the capacitors in the circuit. The influence on the efficiency is pointed out. The use of inductors in SC-based converters is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 3 publications
1
26
0
Order By: Relevance
“…Because of the modular structure of the MMCCC circuit, the required resonant inductance is quite small for each module, thus making it feasible to be realized by parasitic inductance in the circuit. The switching frequency does not need to be pushed to tens of megahertz [96] to utilize the circuit stray inductance. It has been demonstrated that stray inductance is large enough to resonate at around 100 kHz.…”
Section: Ivc Zero Current Switching (Zcs)-mmcccmentioning
confidence: 99%
“…Because of the modular structure of the MMCCC circuit, the required resonant inductance is quite small for each module, thus making it feasible to be realized by parasitic inductance in the circuit. The switching frequency does not need to be pushed to tens of megahertz [96] to utilize the circuit stray inductance. It has been demonstrated that stray inductance is large enough to resonate at around 100 kHz.…”
Section: Ivc Zero Current Switching (Zcs)-mmcccmentioning
confidence: 99%
“…Very low power handling and high EMI are consequences of this kind of operation [6], [7]. Resonant SCCs (RSCs) are SCC alternatives in which the switches current is controlled by placing a small inductor in series with the switching capacitors [6]- [13]. However, not only the converter voltage gain is not adjustable in RSCs [13], but also it varies against load changing [9].…”
Section: Introductionmentioning
confidence: 99%
“…Resonant SCCs (RSCs) are SCC alternatives in which the switches current is controlled by placing a small inductor in series with the switching capacitors [6]- [13]. However, not only the converter voltage gain is not adjustable in RSCs [13], but also it varies against load changing [9]. To provide a fractional voltage gain, many diodes and capacitors ought to be used, which result in an increase of the converter cost, volume and conduction losses [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The idea is based on the authors' earlier proposal of the so-called "switched-capacitor resonant converters" which achieve soft switching by inserting small inductors in series with the switching capacitors. The fundamental problems associated with the so-called "switched-capacitor resonant converters" has been discussed in a recent publication [2]. The most severe limitation is the inability to provide regulation against input voltage changes and transient load changes.…”
mentioning
confidence: 99%
“…Reference [1] however, has been devoted to the historical case of open-loop SC circuits where switching capacitors are fully charged in each intermediate step, thus providing no output regulation. The basic problem of losing voltage regulation in such historical SC converter circuits has been discussed in [2] in terms of partial and full charging of the switching capacitors. The key idea is that the capacitors should never be fully charged at the nominal duty cycle in order to allow the converter to "maneuver" over an adequate range of voltage ratio in case of line voltage changes and load transients.…”
mentioning
confidence: 99%